2000
DOI: 10.1093/ndt/15.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Japanese dialysis patients with an A-to-G mutation at nucleotide 3243 of the mitochondrial tRNALeu(UUR) gene

Abstract: We found that a mitochondrial gene mutation at nucleotide 3243 was present in one dialysis patient with NIDDM and deafness. The prevalence of this mutation was found to be below 1% in diabetic end-stage renal disease patients in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
13
2
Order By: Relevance
“…In adulthood, the A3243G mutation is so far the unique mtDNA mutation responsible for kidney disease. In two studies of Japanese diabetic patients on regular dialysis, its prevalence reached 0.8 and 5.9%, respectively (40,41). In a French diabetic population, renal involvement of various severities was found in 28% of 54 patients with A3243G mutation after a 12-yr follow-up (22).…”
Section: Discussionmentioning
confidence: 97%
“…In adulthood, the A3243G mutation is so far the unique mtDNA mutation responsible for kidney disease. In two studies of Japanese diabetic patients on regular dialysis, its prevalence reached 0.8 and 5.9%, respectively (40,41). In a French diabetic population, renal involvement of various severities was found in 28% of 54 patients with A3243G mutation after a 12-yr follow-up (22).…”
Section: Discussionmentioning
confidence: 97%
“…The mtDNA 3243A3 G point mutation is regarded as another form of familial FGS. This mutation has been observed in approximately 0.6 to 1.5% of patients with type 2 diabetes mellitus (25,33) and in approximately 16.3/ 100,000 individuals in the general adult population (34). Guillausseau et al (35) reported that 28% of patients with type 2 diabetes mellitus and the mtDNA 3243A3 G point mutation exhibited kidney disease, and renal histologic analyses for three patients who underwent renal biopsies demonstrated FGS.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent accumulation of an A3 G transition at mtDNA position 3243 has also been reported (20 -22). Blood cells often exhibit low levels of mutated mtDNA, with mutations such as the common deletion and the 3243A3 G transition (23)(24)(25). In general, glomerular epithelial cells are regarded as terminally differentiated cells that do not proliferate (26 -28).…”
mentioning
confidence: 99%
“…In the present study, one patient (case 1), who had the A3243G mutation at a relatively high percentage in mtDNA in leukocytes, had SNHL and cardiomyopathy but not DM. Cardiac involvement has been reported in patients with the mutation and DM/SNHL (Shiotani et al 1998;Yamagata et al 2000). Another organ that has been relatively frequently reported to be involved in patients with the mutation is the kidney (Cheong et al 1999;Nakamura et al 1999;van den Ouweland et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work showed that the identical mutation is also causative for maternally inherited diabetes associated with deafness van den Ouweland et al 1992van den Ouweland et al , 1994, and the name MIDD (maternally inherited diabetes and deafness) was proposed for this syndrome (van den Ouweland et al 1994(van den Ouweland et al , 1995. Furthermore, the A3243G mutation was shown to be a cause of an overlapping syndrome of MERRF (myoclonic epilepsy with ragged-red fibers) and PEO (progressive external ophthalmoplegia) (Verma et al 1996), PEO (Koga et al 2000;Pang et al 1999), Kearns-Sayre syndrome (Pang et al 1999), Leigh syndrome (Koga et al 2000), progressive nondiabetic kidney disease (Cheong et al 1999;Jansen et al 1997), and cardiac diseases (Shiotani et al 1998;Yamagata et al 2000). Majamaa et al (1998) studied an adult population of 245,201 individuals, and screened for the A3243G mutation in 480 selected subjects who had one or more of following diseases: diabetes mellitus (DM), sensorineural hearing impairment, epilepsy, occipital brain infarct, ophthalmoplegia, cerebral white-matter disease, basal-ganglia calcifications, hypertrophic cardiomyopathy, or ataxia.…”
Section: Introductionmentioning
confidence: 99%